Hubungan Strategi Koping Terhadap Resiliensi Caregiver Keluarga Pasien Skizofrenia di Klinik Jiwa UPT RSUD Madani Provinsi Sulawesi Tengah: Penelitian - Yusril JP Besi; Rahmat Doko; Elin Hidayat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Caregivers or family members who take care of people with schizophrenia (PWS) often experience a heavy psychological burden, stress, and high social pressure. These conditions can affect their ability to use adaptive coping strategies and decrease their level of resilience. Good resilience is essential for caregivers to adapt, endure challenges, and perform their role optimally. Objective: This study aims to determine the relationship between coping strategies and resilience among family caregivers of schizophrenia patients at the Mental Health Clinic of UPT RSUD Madani, Central Sulawesi Province. Methods: This research used a quantitative analytical method with a cross-sectional approach. The study population consisted of caregivers of schizophrenia patients at the mental health clinic of UPT RSUD Madani Palu. The sample was calculated using the Fisher Z transformation formula, resulting in 48 respondents. The sampling technique used was purposive sampling. The instruments used were the adapted Brief COPE questionnaire to measure coping strategies and the Connor-Davidson Resilience Scale (CD-RISC) 25 items to measure resilience. Data were analyzed using univariate and bivariate analysis with the Chi-Square test. Results: The results showed a significant relationship between coping strategies and resilience among caregivers of schizophrenia patients (p = 0.000; p < 0.05). Conclusion: There is a significant relationship between coping strategies and resilience among caregivers of people with schizophrenia. Caregivers who employ adaptive coping strategies tend to have higher levels of resilience. Efforts to improve adaptive coping abilities through education, family counseling, and the establishment of support groups are needed to strengthen the psychological resilience of caregivers in providing care for schizophrenia patients.